2018
DOI: 10.2460/ajvr.79.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Use of high-field and low-field magnetic resonance imaging to describe the anatomy of the proximal portion of the tarsal region of nonlame horses

Abstract: OBJECTIVE To use high-field and low-field MRI to describe the anatomy of the proximal portion of the tarsal region (proximal tarsal region) of nonlame horses. SAMPLE 25 cadaveric equine tarsi. PROCEDURES The proximal portion of 1 tarsus from each of 25 nonlame horses with no history of tarsal lameness underwent high-field (1.5-T) and low-field (0.27-T) MRI. Resulting images were used to subjectively describe the anatomy of that region and obtain measurements of the collateral ligaments of the tarsocrural joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Studies have compared low-and high-field MRI of cadaver specimens and found that although image resolution varies, the appearance of normal tissue is by and large similar when excluding magic angle artifact. 21,22 With the exception of cartilage disease, gross pathology was also detected with both modalities 22 In this survey, abnormalities previously reported in the context of the imaging diagnosis of suspensory ligament disease such as adhesion formation, 16,23 ultrasonographic divergence, 24 or changes to the MRI appearance of muscle/adipose tissue bundles 23 were given low prevalence and/or significance ratings, suggesting that these are either uncommon, not perceived to be important, or not being recognized. Given the recently suggested association of muscle/adipose tissue signal change with lameness and histopathological measures of disease, 23 which had not been observed as a feature of proximal suspensory desmitis in previous high-field MRI studies, 13,14,17 a better understanding of this feature, its prevalence, and significance is required.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Studies have compared low-and high-field MRI of cadaver specimens and found that although image resolution varies, the appearance of normal tissue is by and large similar when excluding magic angle artifact. 21,22 With the exception of cartilage disease, gross pathology was also detected with both modalities 22 In this survey, abnormalities previously reported in the context of the imaging diagnosis of suspensory ligament disease such as adhesion formation, 16,23 ultrasonographic divergence, 24 or changes to the MRI appearance of muscle/adipose tissue bundles 23 were given low prevalence and/or significance ratings, suggesting that these are either uncommon, not perceived to be important, or not being recognized. Given the recently suggested association of muscle/adipose tissue signal change with lameness and histopathological measures of disease, 23 which had not been observed as a feature of proximal suspensory desmitis in previous high-field MRI studies, 13,14,17 a better understanding of this feature, its prevalence, and significance is required.…”
Section: Discussionmentioning
confidence: 72%
“…Given the lack of clinical studies evaluating high‐field MRI and standing low‐field MRI of the proximal metacarpal/metatarsal region side by side, one cannot assess whether the same diagnostic outcomes can be achieved with both modalities. Studies have compared low‐ and high‐field MRI of cadaver specimens and found that although image resolution varies, the appearance of normal tissue is by and large similar when excluding magic angle artifact . With the exception of cartilage disease, gross pathology was also detected with both modalities but similar diagnostic outcomes should not be expected as practical concerns (patient compliance/positioning) and motion artifact susceptibility during live imaging are major considerations in particular when imaging hindlimbs.…”
Section: Discussionmentioning
confidence: 99%
“…MRI provides brilliant noninvasive 3D images of both the soft and hard structures of the carpus [ 48 ]. Furthermore, it enables the detection of small and obvious lesions without inducing gross structural variations [ 19 , 20 ]. In this study, the MRI of the carpal joint was performed on isolated limbs of donkeys using a 4 mm slice thickness.…”
Section: Discussionmentioning
confidence: 99%
“…It provides high-resolution cross-sectional images with spatial separation of structures, allowing for proper visualization of bony structures without superimposition as in plain X-rays [ 18 ]. MRI is an efficient and significant imaging tool in equine orthopedics that provides multiplane and multislice cross-sectioned copies of the limbs, specifically soft and hard tissues [ 19 , 20 ]. When the results of other analysis imaging means are inconclusive, MRI is highly recommended to verify the various carpal lameness diagnoses [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This profound sensitivity allows prompt and accurate treatment to be prescribed and in turn promoting prevention or protection against further injury. Commonly, forelimb lameness is associated with damage to the fetlock and structures within the hoof, this ranges from subchondral remodelling to navicular oedema and everything in between (Biggi and Dyson, 2018). The level of detail required to identify the causes of lameness are often unobtainable by radiographs or ultrasonography alone, this can be multi-factorial but often due to poor ultrasonic access to the capsule of the hoof and inadequate clarity or reduced radiographic contrast (Mair et al, 2010;Blunden et al, 2010).…”
Section: Diagnostic Applicationmentioning
confidence: 99%